Multiculturalidad y modelos económicos en América Latina: Multiculturalism and economic models in Latin America - Huertas Vilca, Karla Stefanny; Maguiña Rivero, Omar Fabricio; Durand Azcárate, Luis Augusto (Revista de Filosofía, 2021)
This paper aims to analyze the economic models applied throughout history in Latin America, emphasizing the development of the neoliberal model, understood as the preference for markets over cultural norms; bringing up the substitution of the company name for an economy abundant in capital and accumulated wealth in a sector of the population. Thus, guaranteeing the conversion of social rights into commercial services, where its main purpose is the search for macroeconomic balances at the expense of marginalization, discrimination and violation of the rights of populations that represent multiculturalism in the region. That is why, the need to search for balance focused on individual and collective safeguarding in the face of abuse and capitalist arbitrariness. The present investigation assumes a theoretical-philosophical position; however, it recognizes the confluence in the political, cultural and ecological impact. Scenarios that have concentrated problems that lead to the destruction of the diversity of peoples in the region, disrupting the value and human dignity by pursuing a dominant culture, the assimilation of other vulnerable ones through the imposition of knowledge, beliefs and ways of life different from yours. For this reason, the importance of an economic model reoriented to the multidimensional compression of its impact on the environment is recognized, creating a horizontal coexistence with relegated and marginalized cultures in society.